Exercise therapy in diabetic patients - Kinsuke Tsuda; Yusuke Tsuda; Yuzo Sato; Akihiko Ishihara (Japanese Society of Physical Fitness and Sports Medicine, 2014)
The prevalence of diabetes in the population continues to increase worldwide. The complications of diabetes cause morbidity and mortality, and the cost of managing diabetes has become an important social problem in health economics. Strategies for the prevention and treatment of diabetes are therefore very important, and along with pharmacological and diet approaches, exercise plays a fundamental role. This review outlines the biological and clinical aspects of exercise therapy in patients with diabetes, and highlights the recent advances in research on this topic. The mechanisms by which exercise can reduce insulin resistance are described, along with the effects of exercise on plasma insulin and glucose levels, as well as on changes in muscle fiber types that occur in diabetes. Regarding clinical aspects of exercise in patients with diabetes, recent Japanese practice and physical activity guidelines are discussed, and the latest research into diabetes and exercise, including the role of myokines and the effects of exercise on lifespan and cognition are described.